Developing a Maqasid-based performance measurement index for Islamic banks - Islam, Rafikul (2017)
The upsurge of Islamic banking has always been seen from the perspective of growth of assets and market share which somehow depict the profit oriented nature of a business entity. “Riba free banking” seems to be the only factor that differentiates Islamic banking from its conventional counterpart. As a result, the true objective of Islamic banks which is the fulfillment of “Maqasid al Shariah” have not been formally addressed. Currently, the Islamic banks are being evaluated by using the same conventional yardstick which mainly focuses on financial measures. Hence, a paradigm shift is required in the Islamic Banking industry where the framework of Maqasid al Shariah will be used for performance evaluation. The objective of this study is to develop a Maqasid al Shariah based Index by operationalizing the Maqasid framework of Imam al Ghazali and Abu Zaharah. At first, semi-structured interviews of experts on Islamic banking and finance (IBF) have been conducted to select the variables for index. Afterwards, a focus group discussion was arranged consisting five experts in IBF to validate the selected variables. Then analytic hierarchy process (AHP) is employed to determine the relative importance and weight of each Maqasid item and sub-items. The respondents in this case are the industry experts, Shariah scholars and academics. Based upon this, an index is developed to rank the performance of Islamic banks in Malaysia. This study contributes to the theory of Maqasid al Shariah with respect to banking performance evaluation by identifying the necessary variables to operationalize Maqasid items. The Maqasid-based index is expected to assist the stakeholders to measure how far the performance of IB’s are in line with Maqasid al shariah.